(untitled) (Psicologia USP, 1991)
The purpose of this essay is to analyse the rôle of (i) ways of recording, and (ii) quantification, in behavioral diagnosis. Emphasis is placed on quantification. Some other usually neglected aspects of behavioral diagnosis arc discussed, e. g., avaliation of client's complains.